2022
DOI: 10.1016/j.bja.2021.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Utility of unidimensional and functional pain assessment tools in adult postoperative patients: a systematic review

Abstract: Background: In this systematic review we aimed to appraise the evidence relating to the measurement properties of unidimensional tools to quantify pain after surgery. Furthermore, we wished to identify the tools used to assess interference of pain with functional recovery. Methods: Four electronic sources (MEDLINE, Embase, CINAHL, PsycINFO) were searched in August 2020. Two reviewers independently screened articles and assessed risk of bias using the COnsensus-based Standards for the selection of health Measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 76 publications
(191 reference statements)
0
34
0
Order By: Relevance
“…The definition of recovery time can vary. In addition to measuring pain, tools to assess interference of pain with functional recovery should be used 36. We defined the duration of the postoperative recovery to be dependent on three endpoints: pain at rest, pain on swallowing and the regular use of analgesics.…”
Section: Discussionmentioning
confidence: 99%
“…The definition of recovery time can vary. In addition to measuring pain, tools to assess interference of pain with functional recovery should be used 36. We defined the duration of the postoperative recovery to be dependent on three endpoints: pain at rest, pain on swallowing and the regular use of analgesics.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should include disease-specific patient-reported outcome measures and focus on analgesia as it relates to function due to the limitations in, and risks of, unidimensional pain assessment tools such as the NRS. 26,27 This prospective cohort study is limited in its external validity as the intervention was only studied in a small subset of patients seen by spine surgeons. However, the results are comparable with a similar protocol in general surgery procedures, such as laparoscopic cholecystectomy and inguinal hernia repair, 22 and as such it is reasonable to assume it may be applicable to other relatively minor surgical procedures in other specialties.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should include disease-specific patient-reported outcome measures and focus on analgesia as it relates to function due to the limitations in, and risks of, unidimensional pain assessment tools such as the NRS. 26 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…4 Among the different assessment tools for pain perception, one is Visual Analogue Scale (VAS) for pain with 10 scores with 0=no pain and 10 worst intolerable pain. [5][6][7] The study is concerned with mean postoperative pain score assessment with use of conventional knot and tie with suture technique in comparison with Ligasure, while keeping analgesics common for both. We found significance of 3.6+1.2 with former and 2.4+1.6 for the later, while in another study, no significant difference was found in postoperative pain score in both surgical techniques, results were 2.1 with use of Ligasure and was 2.6 with conventional technique.…”
Section: Introductionmentioning
confidence: 99%